Acute Changes in Foot Strike Pattern and Cadence Affect Running Parameters Associated with Tibial Stress Fractures - Yong, Jennifer R. (J Biomech, 2018)
Tibial stress fractures are a common and debilitating injury that occur in distance runners. Runners may be able to decrease tibial stress fracture risk by adopting a running pattern that reduces biomechanical parameters associated with a history of tibial stress fracture. The purpose of this study was to test the hypothesis that converting to a forefoot striking pattern or increasing cadence without focusing on changing foot strike type would reduce injury risk parameters in recreational runners. Running kinematics, ground reaction forces and tibial accelerations were recorded from seventeen healthy, habitual rearfoot striking runners while running in their natural running pattern and after two acute retraining conditions: (1) converting to forefoot striking without focusing on cadence and (2) increasing cadence without focusing on foot strike. We found that converting to forefoot striking decreased two risk factors for tibial stress fracture: average and peak loading rates. Increasing cadence decreased one risk factor: peak hip adduction angle. Our results demonstrate that acute adaptation to forefoot striking reduces different injury risk parameters than acute adaptation to increased cadence and suggest that both modifications may reduce the risk of tibial stress fractures.